Horses are worthy of care: Horse sector participants’ attitudes towards animal sentience, welfare, and well-being - Julie M Fiedler; Margaret L Ayre; Sarah Rosanowski; Josh D Slater (Animal Welfare)
Organisations for which sentient animals are central to the business model need to demonstrate the safeguarding of animal welfare and well-being. This requires providing positive experiences for animals which is critical to maintaining the social licence to operate. A cross-sectional survey captured the attitudes of experienced horse sector participants regarding sentience, welfare and well-being. Almost all respondents (99.9%; n = 676/677), believed horses were sentient. Analysis of open-ended responses identified two themes: (1) Sentience is a pathway to understanding the mental state, welfare and well-being of horses; and (2) A moral obligation for humans to consider sentience. Respondents’ observations that horses reacted to stimuli and responded to their surroundings underpinned their belief that horses were sentient. Theme one related to respondents’ understanding of sentience and how sentience informed their interpretations of horse behaviours and the making of inferences regarding the equine mental state. Theme two related to a moral obligation believed to exist towards horses because humans manage the horses’ environment and need to consider the impact of their interactions with horses. These obligations were perceived as responsibilities to consider sentience when determining good welfare and well-being in horse activity settings, when interacting with horses and when training and competing with horses. The results suggested a sophisticated understanding of sentience existed among experienced horse sector participants, who recognised the sentient horse as worthy of care. We propose that leveraging experienced participants’ existing knowledge of sentience could support the implementation of the Five Domains model when updating organisational policies.